2018
DOI: 10.1016/j.jtherbio.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Plastic responses to diel thermal variation in juvenile green sturgeon, Acipenser medirostris

Abstract: Human-induced thermal variability can disrupt energy balance and performance in ectotherms; however, phenotypic plasticity may play a pivotal protective role. Ectotherm performance can be maintained in thermally heterogeneous habitats by reducing the thermal sensitivity of physiological processes and concomitant performance. We examined the capacity of juvenile green sturgeon (Acipenser medirostris) to respond to daily thermal variation. Juveniles (47 days post-hatch) were exposed to either stable (15 ± 0.5 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 86 publications
(117 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, swimming performance was insensitive to a wide range of temperatures, suggesting that sturgeon were responding to the mean temperatures and not the daily peaks (Rodgers, Cocherell, Nguyen, Todgham, & Fangue, 2018). Furthermore, swimming performance was insensitive to a wide range of temperatures, suggesting that sturgeon were responding to the mean temperatures and not the daily peaks (Rodgers, Cocherell, Nguyen, Todgham, & Fangue, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, swimming performance was insensitive to a wide range of temperatures, suggesting that sturgeon were responding to the mean temperatures and not the daily peaks (Rodgers, Cocherell, Nguyen, Todgham, & Fangue, 2018). Furthermore, swimming performance was insensitive to a wide range of temperatures, suggesting that sturgeon were responding to the mean temperatures and not the daily peaks (Rodgers, Cocherell, Nguyen, Todgham, & Fangue, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…behaviour, fish species, Hypomesus transpacificus, predator, warming medirostris; Acipenseridae) acclimated to fluctuating temperature conditions (narrow or widely variable) demonstrated no change in upper temperature tolerance. Furthermore, swimming performance was insensitive to a wide range of temperatures, suggesting that sturgeon were responding to the mean temperatures and not the daily peaks (Rodgers, Cocherell, Nguyen, Todgham, & Fangue, 2018). Understanding species-specific responses to increased temperatures as experienced in nature may better inform ecological responses.…”
Section: Introductionmentioning
confidence: 99%
“…tidal flats, tide pools and tidal-mixing fronts, can experience large short-term thermal fluctuations. The responses to short-term cyclic thermal fluctuations vary greatly between ectotherm species and/or physiological processes 1012 . Such thermally fluctuating conditions can increase the metabolic energy demands of some ectotherms, and even result in a failure to maintain physiological processes and performance traits 10,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, younger juveniles (155 dph) may be less vulnerable to high temperatures, as Allen et al (2006a) found swimming performance to be greater at 24°C compared to 19°C. Young juveniles (47 dph) have also been shown to respond to daily thermal fluctuations, with fish exposed to wide temperature fluctuations (11–21°C day −1 ) able to maintain swimming performance across a wider range of temperatures and having improved growth compared to fish maintained at stable temperatures (Rodgers et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies (c.f. Allen et al , 2006b; Rodgers et al , 2018) used constant temperatures, but natural river temperatures with daily fluctuations should be mimicked.…”
Section: Discussionmentioning
confidence: 99%